Developmental pathways of cardiorespiratory fitness from 6 to 15 years of age - Rodrigues, L. P.; Bezerra, P.; Lopes, V. P. (European Journal of Sport Science, 2021)
Most of the information gathered about physical fitness of paediatric populations are cross-sectional, resulting in normative perspectives that account for average values relative to age, but not to a comprehensive understanding of developmental individual trajectories. The aim of this study was to model the longitudinal development of cardiorespiratory fitness of boys and girls from 6 to 15 years of age, using an individual centred approach. Two hundred twenty-nine school children (128 boys; 101 girls) were followed on their 20 metres shuttle run test (20mSRT) results from 6 to 15 years of age. Annual measurements were made during the four years of primary school, and again at grade 9th or 10th. Individual trajectories of 20mSRT development were modelled and grouped according to their similarities of change in three different developmental pathways that were included in subsequent hierarchical nested models for testing each sex developmental model of cardiorespiratory fitness. Final models including the developmental pathways showed better deviance statistics (p < .001). Interindividual slope variances were almost zero, and statistically non-significant (0.05 boys 0.01 girls; p > .50), meaning these models capture well the existing variability, in respect to the rate of change. Individual pathways of change in the performance of 20mSRT test can be detected in childhood and adolescence. Additionally, all individual`s developmental trajectories in 20mSRT can be described using three significantly different slopes. These pathways are indicative of a high, average, or low rate of change in performance over the years and differ from the normative approach.